Improved methane dehydroaromatization reaction over Mo and Cr co-doped ZSM-5 catalyst. (15th March 2023) - Miyake, Koji; Sumi, Tomoka; Kokuryo, Shinya; Kitamura, Haruna; Hernandez Gaitan, Jose A.; Uchida, Yoshiaki; Nishiyama, Norikazu
Abstract : We prepared Mo and Cr co-loaded ZSM-5 (Mo/Cr/ZSM-5) by a sequential impregnation method and applied it to methane dehydroaromatization (MDA) reaction. Abstract : We prepared Mo and Cr co-loaded ZSM-5 (Mo/Cr/ZSM-5) by a sequential impregnation method and applied it to methane dehydroaromatization (MDA) reaction. The Mo/Cr/ZSM-5 showed better catalytic performance on MDA reaction than only Mo-loaded ZSM-5.